2012
DOI: 10.3899/jrheum.120541
|View full text |Cite
|
Sign up to set email alerts
|

Infliximab is Associated with Improvement in Arterial Stiffness in Patients with Early Rheumatoid Arthritis — A Randomized Trial

Abstract: MTX plus IFX causes a more significant reduction in PWV than MTX alone in patients with early RA after 6-month treatment, and further improvement may be achieved in patients who continued on longterm tumor necrosis factor-α blockers, suggesting that early, effective suppression of inflammation may prevent progression of atherosclerosis by improving vascular function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 48 publications
0
39
0
3
Order By: Relevance
“…121 The effect of anti-TNF treatment on PWV had been summarized in a recently published systematic review. 122 Two RCTs in patients with early RA (ERA) 123 and AS 124 both reported more favorable results in the anti-TNF-treated groups (ERA, significantly greater PWV reduction in the IFX 1 MTX group than in MTX alone group; AS, PWV remained stable in the GOL group vs significant progression in the placebo group) ( Table I). Observational and case-control studies reported that the PWV either decrease significantly 31,127,140,144 or remained unchanged 133,138,142 after 1.5 to 12 months of anti-TNF treatment in patients with RA.…”
Section: Mechanism Of Inflammation In Cvd In Inflammatorymentioning
confidence: 94%
See 1 more Smart Citation
“…121 The effect of anti-TNF treatment on PWV had been summarized in a recently published systematic review. 122 Two RCTs in patients with early RA (ERA) 123 and AS 124 both reported more favorable results in the anti-TNF-treated groups (ERA, significantly greater PWV reduction in the IFX 1 MTX group than in MTX alone group; AS, PWV remained stable in the GOL group vs significant progression in the placebo group) ( Table I). Observational and case-control studies reported that the PWV either decrease significantly 31,127,140,144 or remained unchanged 133,138,142 after 1.5 to 12 months of anti-TNF treatment in patients with RA.…”
Section: Mechanism Of Inflammation In Cvd In Inflammatorymentioning
confidence: 94%
“…122 Two RCTs in patients with ERA did not show any significant change in both groups with or without anti-TNF treatment 123,125 (details of the anti-TNF reagents used and the control groups are depicted in Table I). However, in another RCT in patients with AS, IMT remained unchanged after 6 months of anti-TNF treatment by GOL, whereas a significant increase in IMT was observed in the placebo group.…”
Section: Mechanism Of Inflammation In Cvd In Inflammatorymentioning
confidence: 99%
“…(Table 2) Three randomized, placebo-controlled trials evaluated the effect of biologic anti-inflammatory agents on arterial stiffness in patients with rheumatoid arthritis (RA). Tam et al [54] and Wong et al [55] both reported significant reduction in PWV after 6 months and about 1 year of treatment, respectively, with anti-TNFa agents in combination with methotrexate but not with methotrexate alone. Kume et al found both tocilizumab (an IL-6 receptor antagonist) and anti-TNF agents to be equally effective in reducing cardiac ankle-vascular index after 24 weeks of therapy [56] while McInnes et al found tocilizumab to not reduce PWV significantly after 12 weeks [57].…”
Section: Prospective Studiesmentioning
confidence: 96%
“…76 In a randomized controlled trial of 40 patients with active rheumatoid arthritis, patients treated with methotrexate and infliximab had a greater reduction in aortic stiffness than patients treated with methotrexate alone, which was accompanied by a decrease in rheumatoid arthritis disease activity. 77 In light of the lack of data on how anti-TNF agents might modify the risk of cardio vascular disease in patients with IBD, these findings provide i ndirect evidence of a potential beneficial effect.…”
Section: Ibd-directed Therapymentioning
confidence: 96%